Insight into the thermal shifts of ten fluorescence peaks Y1–Y10 for Sm3+ ions in Y3Al5O12 crystal. (December 2019) - Mei, Yang; Zheng, Wen-Chen; Liu, Hong-Gang
Abstract: The observed linear thermal shifts of ten fluorescence peaks Y1 –Y10 from room temperature to about 1000 K for Y3 Al5 O12 :Sm 3+ (grown by the Czochralski method) were investigated by considering both the static effect owing to lattice thermal expansion and the dynamic effect stemming from electron–phonon interaction. The static effects were acquired by using the pressure dependences of these fluorescence peak positions. The static effects for the ten fluorescence peaks resulted in thermal blue shift, but the dynamic effects for all peaks except Y7 led to thermal red shift. The observed nature of thermal shift (i.e. red or blue) of a fluorescence peak was due to competition between the static and dynamic effects. Based on an approximate treatment, the static parameter A (characterizing the static effect) and electron–phonon coupling parameter α ʹ (characterizing the dynamic effect) for these fluorescence peaks were estimated in the case where thermal shift curves from low temperature to near or higher than room temperature were not measured. Parameters A for all fluorescence peaks and α ʹ for all peaks except Y7 were comparable in sign and magnitude with those of the sharp luminescence peaks of other rare earth ions in crystals and so were deemed to be reasonable. The causes of the exception for α ʹ of Y7 spectral peak (including the very large observed thermal blue shift of this peak) remain unclear. Highlights: Thermal shifts of ten spectral peaks of YAG:Sm 3+ from 293 to 1000 K are studied. Study uses a full expression including both static and dynamic effects. Static and electron–phonon coupling parameters are evaluated even at high temperature. The full expression can indicate either thermal red-shift or blue-shift.